Mediating Disruptive Leaderships And Organizational Culture In Agricultural Corporations: The Role Of Technology Integration - Iyushar Ganda Saputra; Rojuaniah Rojuaniah (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to examine the effect of disruptive leadership and organizational culture on employee performance through ICT integration. The data were collected by using disruptive leadership, organizational culture, ICT implementation, and employee performance instruments from 216 respondents at PTPN 1 Regional 7 through Google Form. The data were analyzed by using Structural Equation Modelling Partial Least Square (SEM PLS). The findings of this study show that disruptive leadership had no effect on employee performance and ICT implementation. Meanwhile, organizational culture affected employee performance and ICT implementation. The ICT implementation affected the employee performance. The use of ICT did not mediate the relationship between disruptive leadership and employee performance. However, the ICT implementation could mediate the relationship between organizational culture and employee performance. Theoretical, practical, and managerial implications of the research findings are also discussed .